Uniform trellis coded quantization for image transmission over noisy channels - Chen, Chang Wen; Sun, Zhaohui (Signal processing. Image communication, 1999)
A combined source/channel coding scheme without explicit error protection is proposed to transmit images through binary noisy channels. Unlike the error protection with re-transmission scheme and error concealment scheme by inserting synchronization codewords to entropy-coded bitstream, the proposed coding scheme employs transform coding, fixed-rate uniform threshold trellis coded quantization (UTTCQ) and optimal bit allocation algorithm (BAA) to organize the bitstream in a way that is less sensitive to channel noise, achieving data compression and error resilience at the same time. An image is first block transformed to the frequency domain and the same frequency components in different blocks are grouped together as a single subsource. Every subsource is then quantized by a uniform threshold trellis coded quantizer constructed based on the mean and variance of the subsource. Steepest descent method and iterative scheme are employed to determine the optimum bit allocation among the subsources subject to the constraints of the average coding rate and allowable bits to each sample. The coding system uses no error protection, no synchronization codewords and no entropy coding. However, it shows decent compression ratio and gracious degradation with respect to increasing channel errors.